1996
DOI: 10.1177/0272989x9601600101
|View full text |Cite
|
Sign up to set email alerts
|

Is Expected Utility Theory Normative for Medical Decision Making?

Abstract: Expected utility theory is felt by its proponents to be a normative theory of decision making under uncertainty. The theory starts with some simple axioms that are held to be rules that any rational person would follow. It can be shown that if one adheres to these axioms, a numerical quantity, generally referred to as utility, can be assigned to each possible outcome, with the preferred course of action being that which has the highest expected utility. One of these axioms, the independence principle, is contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Because "the complexity of any real decision problem defies complete explicit description" (Savage, 1954, p. 107), the probability models below reflect simplified experimental tasks. For instance, although Baron, Beattie, and Hershey (1988) studied a simple case of medical diagnosis, extension of that analysis to actual medical decision making is not straightforward (Cohen, 1996;Baron, 1996). Nor is it straightforward to predict how subjects will interpret an experimental task (McKenzie, Wixted, & Noelle, 2004 (Table 4) in a pair of questions.…”
Section: Properties Of the Sampling Normsmentioning
confidence: 99%
“…Because "the complexity of any real decision problem defies complete explicit description" (Savage, 1954, p. 107), the probability models below reflect simplified experimental tasks. For instance, although Baron, Beattie, and Hershey (1988) studied a simple case of medical diagnosis, extension of that analysis to actual medical decision making is not straightforward (Cohen, 1996;Baron, 1996). Nor is it straightforward to predict how subjects will interpret an experimental task (McKenzie, Wixted, & Noelle, 2004 (Table 4) in a pair of questions.…”
Section: Properties Of the Sampling Normsmentioning
confidence: 99%
“…The value (utility) of the stationary state is defined as the probability p at the indifference situation. SG is regarded as a valid operationalisation of the von Neuman-Morgenstern utility gamble (Neumann von and Morgenstern, 1953;Cohen, 1996).…”
Section: Standard Gamble (Sg )mentioning
confidence: 99%
“…By the combination of Delphi method, Analytical hierarchy process (AHP), and Utility theory, the development of the DAHP Expected Utility Function in this study presents high objectivity. Cohen indicated that the axioms need not be descriptive to be normative, and they need not be attractive to all decision makers for expected utility theory to be useful for some (Cohen, 1996). Housing Market Search Behavior and Expected Utility Theory: Measuring Preferences for Housing (Smith and Clark, 1982) is a case to establish the decision-making analysis model with Expected Utility Theory for housing issues.…”
Section: Research Methods and Research Designmentioning
confidence: 99%